ANALISIS KEBIJAKAN PENGELOLAAN SUMBERDAYA ALAM BATUBARA DITINJAU DARI ASPEK HUKUM KHUSUSNYA UUPPLH DI KABUPATEN BANJAR DAN TANAH BUMBU - Sri Riyani; Luthfi Fatah; Udiansyah Udiansyah; Yusuf Azis (Universitas Lambung Mangkurat, 2013)
The research was doing to answer the research questions: Is the policy of management of natural resources coal in accordance with UUPPLH and How the implementation of UUPPLH in natural resources coal management policy. This research aims to know: (a) How the implementation of UUPPLH in the management of natural resources coal, (b) How the differences implementation of UUPPLH in management of natural resources coal in the Banjar and Tanah Bumbu Regency, (c) What kinds of constraints encountered in UUPPLH implementation at Banjar and Tanah Bumbu Regency. This research is a survey research field using purposive sampling technique to determine informant as many as 18 people (DPRD, BLHD, NGOs, Mining companies of PKP2B and IUP). Techniques of data colletion conducted by interviews and observations, then the analysis by the method of scoring, descriptive analysis and document analysis. The result showed that for the implementation of UUPPLH in the management of natural resources coal in Banjar and Tanah Bumbu Regency are divided into six aspects (Planning, Utilization, Controlling, Maintenance, Supervison, and Law Enforcement). The different of implementation between Banjar and Tanah Bumbu Regency visible in aspects of Law Enforcement, Banjar (Good) and Tanah Bumbu (Very Good). Constraints encountered in UUPPLH implementation in two Regencies are restricted budget, restricted of government human resources in guarding the UUPPLH implementation, lack of awareness of government and business to the environment, low access to natural resources and environmental information and reporting mechanism of environmental issues for the community, weakness of Law Enforcement issues not in accordance with UUPPLH.